Розробка та впровадження web-застосунку оцінки складності алгоритмів - Безгодков, С. Р. (ХНУРЕ, 2024)
The project involves the development and implementation of a web-based application for assessing algorithm complexity. This application will consist of both frontend and backend components, enabling users to analyze the complexity of various algorithms through a user-friendly interface. By providing tools for assessing algorithmic complexity, the application aims to support developers in optimizing their code and improving overall system performance.
Keywords: оцінка алгоритмів; web-застосунок; розробка системи; впровадження платформи; аналіз складності